2023
DOI: 10.1021/acsanm.3c01776
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Spectroscopy on Selectively Adsorbed Plasmonic Nanostructures Using Polar Surface Arrays

Abstract: This paper introduces an approach that enables highly adjustable surface adsorption of single plasmonic nanostructures using polar surface arrays. The plasmonic nanostructures are made from DNA origami and functionalized with gold nanoparticles for surface-enhanced spectroscopic techniques. To ensure that the contribution of individual nanostructures to the measured signal can be detected without any interference from the surrounding structures, we aimed to control the distance and set a minimum gap between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Bottom-up assembly based on DNA origami can also be combined with top-down lithography [70]. Martynenko et al demonstrated a method for the precisely targeted placement of various shapes of DNA origami on the micrometer to millimeter scale [71].…”
Section: D Arraysmentioning
confidence: 99%
“…Bottom-up assembly based on DNA origami can also be combined with top-down lithography [70]. Martynenko et al demonstrated a method for the precisely targeted placement of various shapes of DNA origami on the micrometer to millimeter scale [71].…”
Section: D Arraysmentioning
confidence: 99%